Videofluoroscopic Swallowing Study Findings Associated With Subsequent Pneumonia in Patients With Dysphagia Due to Frailty - Chang, Min Cheol; Kwak, Soyoung (Frontiers in Medicine, 2021)
Dysphagia in frailty or deconditioning without specific diagnosis that may cause dysphagia such as stroke, traumatic brain injury, or laryngeal pathology, has been reported in previous studies; however, little is known about which findings of the videofluoroscopic swallowing study (VFSS) are associated with subsequent pneumonia and how many patients actually develop subsequent pneumonia in this population. In this study, we followed 190 patients with dysphagia due to frailty or deconditioning without specific diagnosis that may cause dysphagia for 3 months after VFSS and analyzed VFSS findings for the risk of developing pneumonia. During the study period, the incidence of subsequent pneumonia was 24.74%; regarding the VFSS findings, (1) airway penetration (PAS 3) and aspiration (PAS 7 and 8) were associated with increased risk of developing pneumonia, and (2) the functional dysphagia scale (FDS) scores of the patients who developed subsequent pneumonia were higher than those of the patients who did not develop subsequent pneumonia. Our study findings might assist clinicians in making clinical decisions based on the VFSS findings in this population.